Pengembangan UMKM melalui Pendampingan Branding Kemasan dan Pemasaran Digital di Desa Batumarta 1, Kecamatan Lubuk Raja (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in improving the economy of rural communities, but still face various obstacles, particularly in packaging branding and marketing. Snack MSMEs in Batumarta 1 Village, Lubuk Raja District, have good product potential, but are not yet supported by a strong brand identity, attractive packaging design, and optimal use of digital marketing. This community service activity aims to support MSME development through assistance with packaging branding and digital marketing. The implementation method includes observing MSME conditions, socializing the importance of branding and digital marketing, assistance in creating brand identities and product packaging designs, and assistance with promotions through social media. The results of the activity show an increase in MSME understanding of the importance of packaging branding and digital marketing, as well as improvements in the appearance of product packaging to be more attractive and have a brand identity. In addition, MSMEs have begun to utilize social media as a means of product promotion. This activity is expected to expand marketing reach, increase product competitiveness, and support the sustainability of MSMEs in Batumarta 1 Village, Lubuk Raja District.